Status of Biodiversity in West Bengal: Threat to Conservation and Scope of Restoration - Basu, Ranjan (National Geographical Journal of India, 2022)
Despite wide scale deforestation during the colonial and post-colonial periods in the name of economic development, the populous state of West Bengal located in eastern India, still maintains three different forest types in northern hills and piedmont areas, western plateau and its fringe areas as well as littoral forest of the of the Ganga delta. Aquatic ecosystems of the water bodies and wetland, snow and rain fed rivers along with brackish estuaries have diversified the landscape. Expansion of arable land, human settlements and transport arteries has truncated luxurious forests on one hand and taken its toll on floral and faunal diversity of wild terrestrial and aquatic environ on the other. Introduction of high yielding varieties of paddy and hybrid vegetables has led to shrinkage of the biodiversity base in the agrarian landscape too. Transformation of land use has negative impact on the nesting prospect of the birds whose species diversity is also at stake. In-situ conservation of biodiversity is a challenging task now either for the authorities or for the concerned scientists.